Familial risk of childhood cancer and tumors in the li‐fraumeni spectrum in the utah population database: Implications for genetic evaluation in pediatric practice. Issue 10 (12th June 2013) - Curtin, Karen; Smith, Ken R.; Fraser, Alison; Pimentel, Richard; Kohlmann, Wendy; Schiffman, Joshua D.
<x xml:space="preserve">Abstract</x> We used the Utah Population Database to examine risk of cancer in relatives of 4, 482 pediatric cancer cases (≤18 years old) diagnosed from 1966 to 2009 compared to matched population controls. We quantified cancer risk in relatives of children with cancer to determine evidence of familial aggregation and to inform risk assessment and counseling for families. Odds ratios that reflect risk were obtained using conditional logistic regression models adjusting for number of biological relatives, their degree of genetic relatedness and their person‐years at risk. First‐degree relatives (primarily siblings) of pediatric cases faced a twofold increased risk of a cancer diagnosis before age 19, which extended to their second‐degree relatives (p < 10−4, respectively). Furthermore, first‐degree relatives of children diagnosed before age 5 had a 3.6‐fold increased risk of developing pediatric cancer (p < 10−7), second‐degree relatives of very young (under age 5) cases were at 2.5‐fold risk (p < 10−4) and third‐degree relatives were at twofold risk (P < 10−3) of childhood cancer. Although first‐degree relatives of pediatric cases have a slight increased risk of adult tumors, when they do develop cancer they have a 1.7‐fold risk of developing a tumor in the Li‐Fraumeni spectrum. Our findings support the hypothesis of familial aggregation in pediatric cancer and suggest that a higher percent of childhood cancers may be related to hereditary syndromes than are adult cancers. We encourage the collection of a family medical history that is routinely updated for all pediatric cancer patients, and that families with early‐onset adult cancers or clusters of several cancers are referred for genetic counseling.